2015
DOI: 10.1016/j.cell.2015.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Gateway Arch to the RNA Exosome

Abstract: The RNA exosome degrades many different RNAs. Thoms et al. now fill an important gap in our understanding of how the exosome recognizes distinct subsets of target RNAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…S6A), similar to results reported in Arabidopsis (Abbasi et al, 2010;Lange et al, 2011;Hang et al, 2014;Sikorski et al, 2015;Shanmugam et al, 2017). The results suggested that active polyadenylationdependent RNA processing systems, such as those mediated by the TRAMP (Jia et al, 2011;Lange et al, 2014) and nuclear RNA exosome (LaCava et al, 2005;Houseley et al, 2006;Doma and Parker, 2007;Lange et al, 2009;Losh and van Hoof, 2015;Sikorski et al, 2015;Thoms et al, 2015), exist in rice and take part in pre-18S rRNA processing.…”
Section: Identification Of Pre-18s Rrna Intermediates For the Pre-40ssupporting
confidence: 84%
See 1 more Smart Citation
“…S6A), similar to results reported in Arabidopsis (Abbasi et al, 2010;Lange et al, 2011;Hang et al, 2014;Sikorski et al, 2015;Shanmugam et al, 2017). The results suggested that active polyadenylationdependent RNA processing systems, such as those mediated by the TRAMP (Jia et al, 2011;Lange et al, 2014) and nuclear RNA exosome (LaCava et al, 2005;Houseley et al, 2006;Doma and Parker, 2007;Lange et al, 2009;Losh and van Hoof, 2015;Sikorski et al, 2015;Thoms et al, 2015), exist in rice and take part in pre-18S rRNA processing.…”
Section: Identification Of Pre-18s Rrna Intermediates For the Pre-40ssupporting
confidence: 84%
“…In eukaryotic cells, aberrant rRNA biogenesis activates RNA quality control in the nucleus, which triggers higher polyadenylation of certain rRNA intermediates and by-products catalyzed by the Trf/Air/Mtr4 polyadenylation complex (TRAMP; Jia et al, Lange et al, 2014). These intermediates are degraded sequentially by the nuclear exosome complex (LaCava et al, 2005;Houseley et al, 2006;Doma and Parker, 2007;Lange et al, 2009;Losh and van Hoof, 2015;Thoms et al, 2015). Dysfunction of ribosomal biogenesis (Gallagher et al, 2004;Ferreira-Cerca et al, 2005Tafforeau et al, 2013) results in severe developmental defects in higher plants (Byrne, 2009;Fujikura et al, 2009;Horiguchi et al, 2011;Weis et al, 2015aWeis et al, , 2015b and serious genetic diseases in mammals (Choesmel et al, 2007;Narla and Ebert, 2010;McCann and Baserga, 2013;Sondalle and Baserga, 2014;Bai et al, 2016).…”
mentioning
confidence: 99%
“…Specifically, ZCCHC8 CTD interacts with a highly conserved surface at the base of the helicase core modules, unique from the binding sites reported for TRAMP subunits Trf4p and Air2p. While NEXT and TRAMP subunits contact MTR4 through the helicase core, several exosome partners are recruited to MTR4 via its arch domain ( 43 ). Hence, in addition to being an RNA helicase, MTR4 serves as an interaction hub, providing a platform for multiple exosome accessory factors to access the exosome.…”
Section: Discussionmentioning
confidence: 99%
“…118,131−134 Interestingly, the Air2 contacts with the Mtr4 arch resemble those of Utp18 and Nop53, suggesting that these adaptor proteins may compete with Air2 for Mtr4 binding. 118,119 The N-terminus of Trf4 also interacts with the Mtr4 helicase core, with Trf4/Air2 positioned such that RNA could thread from Mtr4 to the Trf4 active site. 118 3.3.3.2.…”
Section: Role Of the Yeast Nuclear Exosome Nucleases In Ncrna Surveil...mentioning
confidence: 99%
“…Both Trf4 and Air2 contact Mtr4. Air2 interacts with both the Mtr4 helicase domain and the arch domain, with the contacts to the Mtr4 arch resembling those of Nop53 and Utp18. , (C) For RNA polymerase II transcripts, the Nrd1–Nab3 heterodimer of the Nrd1–Nab3–Sen1 complex recognizes short motifs on the nascent ncRNA. Nrd1 also interacts with the C-terminal domain of the large subunit of the polymerase.…”
Section: The Rna Exosomementioning
confidence: 99%